2022
DOI: 10.51821/85.2.9680
|View full text |Cite
|
Sign up to set email alerts
|

First-line therapies for H. pylori infection in Italy: a pooled-data analysis

Abstract: Background: Curing H. pylori infection remains challenging, and the use of most effective first-line therapy represents a therapeutic cornerstone. To monitor the efficacy of first-line therapies in Italy, we designed a systematic review with pooled- data analysis of data published in the last 15 years. Methods: The search was focused on standard regimens and adult patients. Studies that included modified therapy regimens, pediatric patients, case series with less than 5 patients, and those in language other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
2
0
0
Order By: Relevance
“…Indeed, the updated Italian and European guidelines, recently published in 2022, recommended that the duration of CT has to be 14 days 12,27 . The eradication rates found in our study were also comparable to those reported in a review evaluating the effectiveness of empirical first lines in Italy, suggesting the reproducibility of our results 28 . Similarly, a Hp‐EuReg study performed over 21,000 treatment‐naïve patients encompassing 27 European countries and assessing the prescriptions and effectiveness trends of first‐line empirical therapy reported that only quadruple therapies lasting at least 10 days were able to achieve over 90% eradication rates, in line with current study results 17 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the updated Italian and European guidelines, recently published in 2022, recommended that the duration of CT has to be 14 days 12,27 . The eradication rates found in our study were also comparable to those reported in a review evaluating the effectiveness of empirical first lines in Italy, suggesting the reproducibility of our results 28 . Similarly, a Hp‐EuReg study performed over 21,000 treatment‐naïve patients encompassing 27 European countries and assessing the prescriptions and effectiveness trends of first‐line empirical therapy reported that only quadruple therapies lasting at least 10 days were able to achieve over 90% eradication rates, in line with current study results 17 .…”
Section: Discussionsupporting
confidence: 90%
“…12,27 The eradication rates found in our study were also comparable to those reported in a review evaluating the effectiveness of empirical first lines in Italy, suggesting the reproducibility of our results. 28 Similarly, a Hp-EuReg study performed over 21,000 treatment-naïve patients encompassing 27 European countries and assessing the prescriptions and effectiveness trends of first-line empirical therapy reported that only quadruple therapies lasting at least 10 days were able to achieve over 90% eradication rates, in line with current study results. 17 Furthermore, a similar Hp-EuReg sub-study focussing on the Spanish cohort, found that the highest first-line effectiveness outcomes were obtained with the 10-day BQT-TSC (95% cure rate by intention-to-treat), with the 14day bismuth-clarithromycin quadruple therapy (PPI-bismuth-clarithromycin-amoxicillin: 91%) and the 14-day non-bismuth CT therapy (PPI-clarithromycin-amoxicillin-metronidazole: 92%), findings that were also in line with present study conclusions.…”
Section: Discussionsupporting
confidence: 81%